Chronic Appendicitis: Possible Differential Diagnosis in Patients with Chronic Abdominal Pain - Iva Ljubas; Ivana Jurca; Dora Grgić (Case Reports in Surgery)
In the emergency department, patients frequently present with abdominal pain, with a variety of different causes ranging from intra-abdominal to extra-abdominal and retroperitoneal pathologies which can affect all age groups. Chronic appendicitis is a rare medical condition characterized by less severe and continuous abdominal pain and a clinical picture lasting longer than 1-2 days and extending over months, even years, and it is not always possible to consider it as a preliminary diagnosis. We represent a case report of chronic appendicitis where the patient’s clinical picture led the diagnostics and treatment in different directions and delayed the diagnosis. Namely, our patient was radiologically diagnosed with a collection of denser content retroperitoneally in the right lower quadrant of the abdomen, which in the first place was not related to possible appendicitis, regarding complaints. The existence of chronic appendicitis is a diagnosis unfamiliar to many clinicians and has no official diagnostic criteria. After diagnosis, treatment usually begins with antibiotics, and the next most common step is surgery. The optimal treatment for this condition is unknown. With this case report, we wish to draw attention to chronic appendicitis as a possible differential diagnosis in patients with chronic abdominal pain.